2012
DOI: 10.1017/s1368980012003461
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between the home food environment, the local food shopping environment and children's fruit and vegetable intake? Results from the Dutch INPACT study

Abstract: Objective: To examine: (i) the association between home availability of fruit and vegetables and children's fruit and vegetable intake; (ii) the association between parental perception of the local food shopping environment and the home availability of fruit and vegetables; and (iii) whether the home availability of fruit and vegetables mediates the association between parental perception of the local food environment and children's fruit and vegetable consumption. Design: Cross-sectional study. Setting: A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
2
32
0
Order By: Relevance
“…In a cross-sectional study, participants who did not have fruit and vegetables always available at home were more likely to eat fruit and vegetables less than recommended compared with participants who always had fruit and vegetables available at home. 24 However, in a study conducted in Puerto Rico, the number of unhealthy or healthy foods at home was not associated with diet quality measured by Healthy Eating Index. 25 Thus, our results are in line with previous studies emphasizing the importance of home food environment, especially regarding foods considered unhealthy.…”
Section: Discussionmentioning
confidence: 92%
“…In a cross-sectional study, participants who did not have fruit and vegetables always available at home were more likely to eat fruit and vegetables less than recommended compared with participants who always had fruit and vegetables available at home. 24 However, in a study conducted in Puerto Rico, the number of unhealthy or healthy foods at home was not associated with diet quality measured by Healthy Eating Index. 25 Thus, our results are in line with previous studies emphasizing the importance of home food environment, especially regarding foods considered unhealthy.…”
Section: Discussionmentioning
confidence: 92%
“…Some prior studies (Kamphuis et al, 2006;Yen et al, 2011;Lazzeri et al, 2013;Tak et al, 2013;van Ansem et al, 2013) suggested that local availability (for example, access to one's own vegetable garden and high food security, accounted for by factors such as local climate, vegetation and soil quality) is an important factor in fruit and vegetable consumption. It must be stated, however, that by this assumption, it was not intended to follow a deterministic ideology.…”
Section: Introductionmentioning
confidence: 99%
“…The home is yet a microenvironment poorly approached in the literature, and among its many factors, it has food access and availability 6,8,11,12 . In Brazil the home environment has been investigated periodically by the Pesquisa de Orçamentos Familiares (POF, Family Budget Survey) 9 , which determined the relative participation of foods and food groups in the total number of calories available at home.…”
Section: Introductionmentioning
confidence: 99%
“…The home food availability has been directly or inversely associated with the intake of many foods and food groups 8,12,14,15 . The presence of energy-dense, nutrient-poor foods at home characterizes the home as an obesogenic environment 2,6 .…”
Section: Introductionmentioning
confidence: 99%